Nuovi orizzonti nel controllo del traffico aereo ENAV affronta la sfida satellitare - Del Duca, Giovanni (GEOmedia, 2008)
New horizons in flight control management: ENAV faces GNSS ENAV – the italian company for air navigation services – is operating on various satellite projects dedicated to flight traffic management, together with other european providers, to resolve increasing flight movements. The actual GNSS – GPS, Glonass and Galileo – already used for maritime, ground and aerial transportation, is ENAV's working objective. ENAV is also active on EGNOS (European Geostationary Navigation & Overlay Service), the satellite augmented system developed by the EU that will provide a lower GPS error margin.